Preparation, Characterization And Properties Of Graphene Filled Epoxy Nanocomposites Produced Using Colloidal Polymerization Method - Abdul Kudus, Muhammad Helmi (2018)
Common issues during fabrication of graphene filled epoxy mostly are dispersion of graphene, re-agglomeration problem and reduction of crosslink density. A different sequence of epoxy composite preparation was performed by mixing oxidized graphene platelets (oGNP) with a curing agent prior to mixing it with epoxy resin. When oGNP was mixed with trimethylhexamethylene diamine (TMD), the condensation reaction between the hydroxyl and amine groups resulted in the formation of a TMD/oGNP colloid. The TMD/oGNP colloid was used to cure epoxy resin. The colloidization eventually improved the dispersion and prevented reagglomeration of graphene in the epoxy resin and resulted in higher crosslink density. A thermogravimetric analysis (TGA) showed that the thermal stability of the epoxy/oGNP system had improved, while the presence of the oGNP gave more stability to the solvent in terms of an increase in the crosslink density. These results showed that the TMD/oGNP colloid mixing sequence was able to enhance the properties of the epoxy composite compared to the conventional method of obtaining graphene filled epoxy nanocomposites. Conventional method refers to fabrication of epoxy/graphene nanocomposites by mixing the graphene into the epoxy resin prior to adding into the curing agent. Epoxy/oGNPcolloidized showed higher crosslink density than Epoxy/oGNPconventional nanocomposite. Epoxy/oGNPcolloidized nanocomposites showed a higher thermal conductivity than an epoxy/oGNPconventional nanocomposite with the same concentration of filler, which is parallel to the crosslink density result. From the observation, in Epoxy/oGNPconventional, where amide network between carboxylic and amine groups were relatively formed, a high crosslink density enhanced the thermal conductivity via phonon transport. Through the analysis, the dielectric properties of epoxy nanocomposites also showed direct relationship with crosslink density as Epoxy/oGNPcolloidized obtained higher dielectric constant value than Epoxy/oGNPconventional. The summary of the study concludes that fabrication of graphene filled epoxy nanocomposites via colloidal polymerization method, enhance the thermal properties, tensile properties and dielectric properties due to the increasing amount of crosslink density and better dispersion of graphene. Further thermal degradation analysis via non-isothermal kinetic study shows an F1 mechanism occurs for epoxy thermal degradation and the Epoxy/oGNPcolloidized achieved the highest lifetime for thermal degradation.